We respect them, and they respect us: The Value of Interpersonal Relationships in Enhancing Student Engagement - Banks, Joanne (My University, 2021)
Attempts to understand the patterns behind student disengagement and early school leaving have traditionally focussed on early school leavers’ individual characteristics. More recently, however, studies have begun to focus on the extent to which early school leaving is shaped by school-level factors, and in particular the central role of teachers and pedagogy, in (dis)engaging students. Studies have consistently shown how negative teacher–student relations can dominate the lives of young people, leading to poor attendance and behavioural issues which often culminate in them disengaging, leaving or being expelled from school. Furthermore, there is a growing interest in the role of pedagogical strategies in enhancing teacher–student relations, increasing student engagement and bringing about more socially just systems of education. Using in-depth qualitative interviews with staff working in a school engagement programme aimed at preventing early school leaving (the School Completion Programme) and young people who have left school early and who are now participating in an alternative education setting in Ireland as well as staff in those settings (the National Youthreach Programme), this paper provides a unique comparison of two approaches to learner engagement. Findings highlight the centrality of caring and respectful relationships between teachers and students across the two programmes. This paper suggests that aspects of the ‘productive pedagogies’ framework are being used to overcome barriers by placing equal emphasis on student wellbeing and formal learning. However, both programmes operate outside ‘mainstream’ education, with little scope for integration with the mainstream system. This paper concludes that at the micro level, the programmes are effective in re-engaging young people with education but argues that this has little impact at a broader level, where mainstream school practices impacting on student disengagement and early school leaving remain unchanged.
PUBLISHED
Keywords: School engagement; Early school leaving; Alternative education; Teacher–student relations; Pedagogy; Inclusive Society; EDUCATION; Education